Dampak Pemberian Konsentrasi Eco Enzyme Dalam Upaya Menekan Insidensi Penyakit Virus Kuning Pada Tanaman Cabai Merah (Capsicum Annuum L.) - tarigan, rio (AGROSUSTAIN, 2025)
This study aims to determine the effect of ecoenzyme in suppressing the intensity of yellow virus disease in red chili plants (Capsicum annum L). This study used a non-factorial Randomized Block Design (RAK), namely with one factor of adding ecoenzyme as an intensity suppressor, consisting of 5 treatment levels, namely E0: control, E1: 10 ml ecoenzyme/liter of water, E2: 20 ml ecoenzyme/liter of water, E3: 30 ml ecoenzyme/liter of water and E4: 40 ml ecoenzyme/liter of water. In carrying out this study, it is necessary to prepare the land, install mulch, fertilize, plant, replant, water, weed and harvest and apply ecoenzyme. The parameters observed were plant height (cm), stem diameter, incidence of red chili plants (Capsicum annum L) on the yellow virus, production or harvest per plot. The provision of ecoenzyme concentration did not significantly affect plant height and stem diameter at the ages of 2, 4 and 6 MST. Addition of nutrients to plants can increase growth, plant immunity to viruses and diseases and increase production for plants. The provision of ecoenzyme concentration affects the diameter of 8 MST and the weight of red chili (Capsicum annum L) per plot. The higher the concentration of ecoenzyme, the better the growth and production of red chili (Capsicum annum L). The provision of ecoenzyme concentration has an effect on suppressing the incidence of yellow virus attacks on red chili (Capsicum annum L) plants